1990
DOI: 10.1002/1097-0142(19901215)66:12<2528::aid-cncr2820661214>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and radiographic evaluation of the murine colon

Abstract: Endoscopic and radiographic techniques have not been widely applicable in the evaluation of chemically induced murine colon cancer. The authors investigated methods of cleansing the rat colon and refined endoscopic and radiographic techniques. They compared total colonoscopy (TC) and air-contrast (ACBE) and single-contrast barium enema (SCBE) findings with those obtained at necropsy in rats with 1,2-dimethylhydrazine (DMH)-induced colon cancer. Gastrograffin enemas with bisacodyl suppositiories showed complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In fact, the former fails to produce a localized solid tumor before resection is carried out, whereas the latter entails a laparotomy. A possible solution was presented 15 years ago when Hull et al [7] showed that it was feasible to perform bowel prep and TC on rats. The authors successfully performed TC on 37 of 39 rats with a pediatric bronchoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the former fails to produce a localized solid tumor before resection is carried out, whereas the latter entails a laparotomy. A possible solution was presented 15 years ago when Hull et al [7] showed that it was feasible to perform bowel prep and TC on rats. The authors successfully performed TC on 37 of 39 rats with a pediatric bronchoscope.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the long murine cecum provides a model for resection, which avoids the need for an anastomosis [1]. Another study showed that total colonoscopy (TC) is feasible in rats [7]. This indicates that a murine model with TC would be ideal for accessing the cecum for mucosal tumor induction.…”
mentioning
confidence: 99%
“…Colonoscopy has been successfully adapted for use in rat models. Using modified bronchoscopes (Hull et al, 1990) or other small-caliber flexible endoscopes (Haughn et al, 2006), total colonoscopy of the rat has been performed successfully, as well as other variations of this procedure (Zhang et al, 1994). Colonoscopy in mice was first attempted with a pediatric cystoscope with good results, although because of anatomic and instrumental limitations, the entire colon to the cecum could not be visualized (Huang et al, 2002).…”
Section: Colonoscopic Techniquementioning
confidence: 99%
“…Several studies have reported on attempts to perform colonoscopy in rats (1)(2)(3)(4)(5)(6)(7)(8)(9). However, in these studies, the rats were either large and old, the bowel was not optimally prepared, a total colonoscopy was not performed or no biopsies were taken.…”
Section: Introductionmentioning
confidence: 99%